GGCX‐related congenital combined vitamin K‐dependent clotting factors deficiency‐1: Description of a fetus with chondrodysplasia punctata - Mathonnet, Alix; Cunat, Séverine; Allias, Fabienne; Caillot, Sandrine; Thonnon, Cyrielle; Till, Marianne; Attié‐Bitach, Tania; Touraine, Renaud; Meunier, Sandrine; Cartellier, Charline; Rossi, Massimiliano; Attia, Jocelyne; et al. (American journal of medical genetics. Part A, 2022)
Congenital combined vitamin K‐dependent clotting factors deficiency (VKCFD) is a rare autosomal recessive disease resulting in hemorrhagic symptoms usually associated with developmental disorders and bone abnormalities. Pathogenic variants in two genes encoding enzymes of the vitamin K cycle, GGCX and VKORC1, can lead to this disorder. We present the case of a male fetus with a brachytelephalangic chondrodysplasia punctata (CDP), absence of nasal bone, growth restriction, and bilateral ventriculomegaly at 18 weeks of gestation. Pathological examination showed a Binder phenotype, hypoplastic distal phalanges, stippled epiphyses, and brain abnormalities suggestive of a brain hemorrhage. Two GGCX pathogenic variants inherited respectively from the mother and the father were identified. To our knowledge, this is the first prenatal description of VKCFD. Even if it remains a rare etiology, which is mostly described in children or adult patients, VKCFD should be considered in fetuses with CDP.